2014
DOI: 10.1089/neu.2013.2985
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Shock Shifts the Serum Cytokine Profile from Pro- to Anti-Inflammatory after Experimental Traumatic Brain Injury in Mice

Abstract: Secondary insults, such as hemorrhagic shock (HS), worsen outcome from traumatic brain injury (TBI). Both TBI and HS modulate levels of inflammatory mediators. We evaluated the addition of HS on the inflammatory response to TBI. Adult male C57BL6J mice were randomized into five groups (n=4 [naïve] or 8/group): naïve; sham; TBI (through mild-to-moderate controlled cortical impact [CCI] at 5 m/sec, 1-mm depth), HS; and CCI+HS. All non-naïve mice underwent identical monitoring and anesthesia. HS and CCI+HS underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 76 publications
1
30
0
Order By: Relevance
“…Experimental studies using a TBI + hemorrhagic shock mouse model have reported increased serum IL-10 levels, but decreased serum IL-6 levels, in the TBI + hemorrhagic shock group compared to isolated TBI (Shein et al, 2014). Varied definitions and models of polytrauma vs. hypotension/shock across clinical and animal studies may account for differences in reported inflammatory profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies using a TBI + hemorrhagic shock mouse model have reported increased serum IL-10 levels, but decreased serum IL-6 levels, in the TBI + hemorrhagic shock group compared to isolated TBI (Shein et al, 2014). Varied definitions and models of polytrauma vs. hypotension/shock across clinical and animal studies may account for differences in reported inflammatory profiles.…”
Section: Discussionmentioning
confidence: 99%
“…This cholinergic anti-inflammatory pathway seems to be critically involved in the control of systemic inflammation and BBB breakdown 119 . Activation of the sympathetic ANS (the ‘sympathetic storm’) after TBI or after an additional hemorrhagic shock can result in massive peripheral release of epinephrine and/or norepinephrine, which causes enhanced, but also reprogrammed and suppressed, immune responses 122124 . After TBI, plasma norepinephrine is associated with a poor outcome, and patients exhibit signs of endotheliopathy and coagulopathy 125 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…These approaches enable kinetic studies of mediator production in TBI animal models [2023]. For example, more than one study reported expression of IL-1β, TNF-α, IL-6, CCL2, CCL3, CXCL1, CXCL2, CXCL8/IL-8, CXCL10, CCR2, CCR5, CXCR4 and CX3CR1within 6 hr of TBI.…”
Section: Inflammatory Reaction Following Tbimentioning
confidence: 99%
“…CCL2 was one of the initial chemokines identified as significantly upregulated within 24 hr in rodent models of TBI at both the mRNA and protein level (Figure 2B) [2023, 41, 42, 60–64]. In situ hybridization, immunohistochemistry and immunofluorescence techniques have shown CCL2 expression in both GFAP-positive astrocytes [60, 61] and cells with macrophage morphology and markers [61, 64].…”
Section: Strategies Aimed At Chemokine Signalingmentioning
confidence: 99%